Nutritional Status Assessment of Adolescent School Going Children in Solukhumbu, Nepal - Sherpa, Ang Tshering; Singh, Neeti; Basnet, Puspa Babu; Sherpa, Mingmar Chhiring (Nepalese Medical Journal, 2019)
Introduction: Around 25% of the total population in Nepal is adolescents (10 to 19 years old). Nutritional programs in Nepal are targeted to young children and pregnant women but neglected among adolescent. Such approach may result poor nutritional status among them. This will lead to poor health outcome and poor academic performance among school children. Thus we aimed to study the nutritional status assessment of adolescent school children in Solukhumbu. Material and Methods: It was a cross sectional study conducted over a period of two and half months (May-July 2018) in a government school at Salleri, Solukhumbu, Nepal. Study participants are 192 students, both male and female, from the age group 10 to 17 years old. Body Mass Index and Height for age was determined by anthropometry. The interview was done by using structured questionnaires to elicit socio-demographic variables. Results: Among 192 students age 10-17 years old, 122(63.5%) were female and 70(36.5%) were male. The majority was Janajati 160(83.3%), Major religion was Hindu 99(51.6%) and Buddhist 93(43.2%), Agriculture was the major occupation of both parents. The literacy rate of the father is 63.2% and mother is 39.9 percent. The majority are underweight 53(27.6%), overweight 11 (5.7%) and obese 3(1.6%). Median Height for Age was 94 (±6.5) with a minimum of 76 and a maximum of 112 and 99(51.6%) are stunted. Conclusions: Stunting, underweight and overweight were prevalent among adolescent children in the school. The causes of these problems should be identified by doing further research and intervention should be done accordingly.